Institutional Theory, Language, and Discourse Analysis: A Comment on Philips, Lawrence, and Hardy - Lok, Jaco; Willmott, Hugh (Academy of Management Review, 2006)
This article presents a commentary on a discursive view of institutions' attempt to remedy the limited analysis of processes of institutionalization, which is noted as a shortcoming repeatedly attributed to institutional theory. The view discussed is that of Professors N. Phillips, T.B. Lawrence, and C. Hardy, as delivered in 2004. They feel that an insufficient amount of attention is being given to the foundational importance of language, and suggest that institutional theory be complemented with insights drawn from discourse analysis. The author points out flaws in the formulation and application of their diagnosis. The author also notes its embrace of realist investigations and its attentiveness to power and politics.